Method for manufacturing positive electrode and method for manufacturing secondary battery

JP2024177427A5Inactive Publication Date: 2025-03-04PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024174634
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-03
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for improving the conductivity of carbon nanotubes (CNTs) in positive electrodes of secondary batteries, such as using nitric acid to open their ends or magnetic separation, either damage the CNT structure or fail to adequately remove catalyst metals, leading to suboptimal conductivity and output characteristics.

Method used

A manufacturing method that involves preparing a CNT paste with a dispersant, applying a magnetic force to separate metals from CNTs, and forming a positive electrode active material layer to enhance conductivity without damaging the CNTs, resulting in a positive electrode with improved output characteristics.

Benefits of technology

The method effectively removes metals from both the surface and interior of CNTs, enhancing their conductivity and resulting in a positive electrode that improves the output characteristics of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a positive electrode which improves output characteristics of a secondary battery.SOLUTION: A method for manufacturing a positive electrode disclosed herein includes: a CNT paste preparing step of preparing a CNT paste containing at least carbon nanotubes (CNTs) and a dispersing agent; a magnetic separating step of exerting a magnetic force on the CNT paste to adsorb metal existing inside the CNTs to separate the CNTs and the metal; a positive electrode active material layer forming paste preparing step of mixing the CNTs subjected to the magnetic separating step, a positive electrode active material and a binder so as to prepare a positive electrode active material layer forming paste; and a positive electrode active material layer forming step of applying the prepared positive electrode active material layer forming paste to a positive electrode current collector to form a positive electrode active material layer on the positive electrode current collector.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode and a method for producing a secondary battery. [Background technology]

[0002] In recent years, secondary batteries (e.g., lithium ion secondary batteries) have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as driving power sources mounted on vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and battery electric vehicles (BEVs).

[0003] The positive electrode of a secondary battery typically has a structure in which a positive electrode active material layer is provided on a positive electrode current collector. A technique is known in which the positive electrode active material layer contains a conductive material to improve the conductivity. For example, Patent Document 1 describes that the short-term output characteristics of a secondary battery can be improved by using carbon nanotubes (CNTs) as one of the conductive materials. Patent Document 1 also describes that the conductivity is improved by opening the ends by a method of oxidizing CNTs in a nitric acid acid solution or the like. Patent Document 2 describes that the electron emission characteristics of CNTs are improved by adsorbing and removing catalytic metals from powdered CNTs by the magnetic force of a magnet. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-92105 A [Patent Document 2] JP 2002-255527 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the results of intensive research by the present inventors, it was found that when the ends are opened by a method of oxidation in an acidic solution of nitric acid or the like, the structure of the CNTs is damaged, and the electrical conductivity of the CNTs may decrease. Furthermore, with the magnetic separation method described in Patent Document 2, a large amount of catalytic metal remains especially inside the CNTs (for example, inside the tube of the CNTs), so there is still room for improvement in improving the electrical conductivity.

[0006] The present invention has been made in view of the above points, and aims to provide a method for producing a positive electrode that improves output characteristics by further improving the electrical conductivity of CNTs. Another object of the present invention is to provide a method for producing a secondary battery having excellent output characteristics by using a positive electrode produced by the production method. [Means for solving the problem]

[0007] The method for producing a positive electrode disclosed herein is a method for producing a positive electrode for a secondary battery, and includes the following steps: a CNT paste preparation step of preparing a CNT paste containing at least carbon nanotubes (CNTs) and a dispersant; a magnetic separation step of applying a magnetic force to the CNT paste to adsorb metal present inside the CNTs and separate the CNTs from the metal; a positive electrode active material layer forming paste preparation step of mixing the CNTs subjected to the magnetic separation step, a positive electrode active material, and a binder to prepare a positive electrode active material layer forming paste; and a positive electrode active material layer forming step of applying the prepared positive electrode active material layer forming paste to a positive electrode current collector to form a positive electrode active material layer on the positive electrode current collector. According to this configuration, the ends of the CNTs can be opened without damaging the structure of the CNTs, and the metal present on the surface and inside of the CNTs can be suitably removed. This further improves the conductivity of the CNTs, and provides a method for producing a positive electrode with excellent output characteristics.

[0008] In a preferred embodiment of the manufacturing method disclosed herein, the CNTs selected in the magnetic separation step are characterized in that the content of the metal is 1.6 mass% or less when the total of the CNTs and the metal is 100 mass%. According to this configuration, it is possible to manufacture a positive electrode that imparts even better output characteristics to a secondary battery.

[0009] In a preferred embodiment of the manufacturing method disclosed herein, the positive electrode active material layer formed in the positive electrode active material layer forming step has a surface area of ​​10 mg / cm2 on both sides. 2 More than 50mg / cm 2 In another preferred embodiment, the positive electrode active material layer formed in the positive electrode active material layer forming step has a porosity of 20% or more and 50% or less. According to this configuration, it is possible to impart excellent output characteristics to the secondary battery.

[0010] The technology disclosed herein also provides a method for producing a secondary battery. The method for producing a secondary battery disclosed herein is characterized in that a secondary battery is constructed using the positive electrode produced by the above-mentioned production method. According to this configuration, a secondary battery having excellent output characteristics can be suitably manufactured. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a flowchart showing a method for producing a positive electrode according to one embodiment. [Diagram 2] FIG. 1 is a vertical cross-sectional view that illustrates a schematic internal structure of a lithium-ion secondary battery according to an embodiment. [Diagram 3] FIG. 2 is a schematic diagram showing the configuration of an electrode body of a lithium ion secondary battery according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the technology disclosed herein will be described below. The embodiment described herein is not intended to limit the technology disclosed herein, as a matter of course. The technology disclosed herein is not limited to the embodiment described herein, unless otherwise specified. Each drawing is drawn typically and does not necessarily reflect the actual product. In addition, in each drawing, the same reference numerals are used for members and parts that perform the same function, and duplicated descriptions may be omitted or simplified. Furthermore, the dimensional relationships (length, width, thickness, etc.) in the drawings do not reflect the actual dimensional relationships. Furthermore, in this specification, the numerical range expressed as "A to B" includes A and B.

[0013] In this specification, the term "secondary battery" refers to a battery that can be repeatedly charged, and includes so-called storage batteries such as lithium ion secondary batteries and nickel-metal hydride batteries, as well as capacitors such as electric double layer capacitors. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0014] Hereinafter, the technology disclosed herein will be described using as an example a method for manufacturing a positive electrode for a lithium ion secondary battery having a wound electrode body and a method for manufacturing the lithium ion secondary battery, but it is not intended to limit the technology disclosed herein to that described in such an embodiment.

[0015] 1. Manufacturing method of the positive electrode Fig. 1 is a flow chart of the manufacturing method of the positive electrode disclosed herein. As shown in Fig. 1, the manufacturing method of the positive electrode disclosed herein includes the following steps: a CNT paste preparation step of preparing a CNT paste containing at least carbon nanotubes (CNTs) and a dispersant; a magnetic separation step of applying a magnetic force to the CNT paste to adsorb metal present inside the CNTs and separate them into CNTs and metals; a positive electrode active material layer forming paste preparation step of mixing the CNTs subjected to the magnetic separation step, a positive electrode active material, and a binder to prepare a positive electrode active material layer forming paste; and a positive electrode active material layer forming step of applying the prepared positive electrode active material layer forming paste to a positive electrode current collector to form a positive electrode active material layer on the current collector.

[0016] (1) CNT paste preparation process In the CNT paste preparation step, at least CNTs and a dispersant are mixed with an appropriate solvent to prepare a CNT paste. In this specification, the term "paste" refers to a mixture in which a part or all of the solid content is dispersed in a solvent, and includes so-called "slurry" and "ink".

[0017] The CNTs used in the CNT paste preparation step are not particularly limited. The CNTs may be, for example, single-walled carbon nanotubes (SWNTs), double-walled carbon nanotubes (DWNTs), or multi-walled carbon nanotubes (MWNTs). These may be used alone or in combination of two or more. Of these, it is preferable to use multi-walled carbon nanotubes. The CNTs may be produced by chemical vapor deposition (CVD), arc discharge, laser ablation, or the like.

[0018] The average length of the CNTs is not particularly limited. If the average length of the CNTs is too long, the CNTs may aggregate and not be uniformly dispersed, and the effect of improving electronic conductivity may decrease. For this reason, the average length of the CNTs is preferably 0.1 μm or more and 50 μm or less, and may be 0.2 μm or more and 30 μm or less, 0.5 μm or more and 10 μm or less, or 0.5 μm or more and 5 μm or less. The average diameter of the CNTs is not particularly limited. The average diameter of the CNTs may be, for example, 0.1 nm or more and 30 nm or less, 1 nm or more and 25 nm or less, 5 nm or more and 20 nm or less, or 10 nm or more and 20 nm or less. The average length and average diameter of the CNTs can be obtained, for example, by taking an electron microscope photograph of the CNTs and averaging the lengths and diameters of 20 or more CNTs, respectively. In addition, the aspect ratio (average length / average diameter) of the CNTs may be, for example, 10 to 1500, and preferably 100 to 1000. The CNTs may be prepared by selecting and purchasing CNTs having the above-mentioned average length, average diameter, etc. from commercially available CNTs.

[0019] The dispersant may be any of the so-called surfactant-type dispersants (also called low molecular weight dispersants), polymer-type dispersants, inorganic-type dispersants, etc. In addition, these dispersants may be any of anionic, cationic, amphoteric, or nonionic. That is, the dispersant may have at least one functional group of anionic group, cationic group, and nonionic group in the molecular structure. The surfactant refers to an amphiphilic substance having a chemical structure in which a hydrophilic portion and a lipophilic portion are bonded by a covalent bond in the molecular structure.

[0020] Specifically, dispersants made of sulfonic acid compounds such as sodium salt of naphthalenesulfonic acid formalin condensate and ammonium salt of naphthalenesulfonic acid formalin condensate, dispersants made of acrylic compounds such as polyacrylates and polymethacrylates, dispersants made of copolymers containing aromatic units such as pyrene and anthracene, triazine dispersants (for example, those containing a carbazole group or a benzimidazolyl group as a heterocyclic group that may have a substituent), polyvinylpyrrolidone (PVP), polyvinylidene fluoride (PVdF), etc. can be preferably used. Among them, dispersants made of copolymers containing aromatic units such as pyrene and anthracene are preferred. Any one of these dispersants may be used alone, or two or more may be used in combination. It is presumed that the metal present inside the CNT becomes slippery when the CNT paste contains the above-mentioned dispersant. As a result, in the magnetic separation process described below, the CNT and the metal can be suitably separated without damaging the structure of the CNT. The content of such a dispersant is not particularly limited, but can be, for example, approximately 1% by mass to 50% by mass when the mass of CNT is taken as 100% by mass.

[0021] The solvent may be an aqueous solvent or a non-aqueous solvent (solvent-based solvent). As the aqueous solvent, a composition consisting of water or a mixed solvent mainly composed of water can be used. As the non-aqueous solvent, for example, N-methylpyrrolidone (NMP) can be preferably used.

[0022] (2) Magnetic separation process In the magnetic separation step, a magnetic force is applied to the prepared CNT paste to separate metals attached to the CNTs from the CNTs. Here, the metals to be separated by magnetic separation are ferromagnetic metals that can be attracted to the magnetic source side when a magnetic force is applied to the CNT paste using a magnetic source (for example, a permanent magnet or an electromagnet). Such ferromagnetic metals attached to the CNTs typically originate from catalytic metals used in manufacturing the CNTs. Examples of such catalytic metals include iron (Fe), chromium (Cr), nickel (Ni), and cobalt (Co). When CNTs containing such metals are used as a conductive material for a positive electrode, there is a risk that the conductivity cannot be fully exhibited. When such metals are removed by treating with an acidic solution such as nitric acid, the structure of the CNTs may be damaged and the conductivity may decrease. In addition, when the dry magnetic separation method is performed on powdered CNTs, the metals present inside the CNTs are not suitably removed, and the conductivity of the CNTs is not sufficiently improved. Therefore, in the manufacturing method disclosed herein, the CNTs and metals are separated by a wet magnetic separation method in which a magnetic source is brought into contact with the CNT paste. As described above, the CNT paste contains a dispersant, which makes the metal present in the CNTs slippery, and the metal present on the surface or inside of the CNTs can be suitably removed. That is, according to the technology disclosed herein, the ends of the CNTs can be opened without damaging the structure, and the metal present inside the CNTs (i.e., inside the cylindrical structure of the CNTs) can be suitably removed. This makes it easier for the electrolyte to penetrate into the inside of the CNTs, improving the movement of, for example, Li ions, and thus a positive electrode that improves the output characteristics of a secondary battery can be manufactured.

[0023] The magnetic separation method is not particularly limited as long as wet magnetic separation can be performed by contacting a magnetic source with the CNT paste. For example, it can be performed using a known wet magnetic separator. The magnet used in the magnetic separation process may be a permanent magnet such as an alnico magnet, a ferrite magnet, or a neodymium magnet, or may be an electromagnet. The shape, size, surface area, and the like of the magnet can be appropriately selected. The magnetic force of the magnet used in the magnetic separation process (magnetic force at the place where it contacts the CNT paste) is preferably about 100 mT or more and 1000 mT or less (for example, 200 mT or more and 800 mT or less, preferably 400 mT or more and 700 mT or less). In addition, the content of metal present on the surface or inside of the CNT can be further reduced by adjusting the number of times the CNT paste is passed through the magnet and the flow rate when passing through the magnet.

[0024] In a preferred embodiment, the CNTs selected in the magnetic separation step have a metal content of 3% by mass or less when the total of the CNTs and the metal is 100% by mass. More preferably, the CNTs selected in the magnetic separation step have a metal content of less than 2% by mass when the total of the CNTs and the metal is 100% by mass, even more preferably a metal content of 1.6% by mass or less, and particularly preferably a metal content of 1.2% by mass or less, for example, a metal content of 1% by mass or less. In particular, when the metal content in the selected CNTs is 1.6% by mass or less, the effect of reducing the output resistance by suitably removing the metal present inside the CNTs is further exerted. The metal content in the CNTs separated in the magnetic separation step can be determined, for example, by subjecting the CNTs to a quantitative analysis using inductively coupled plasma mass spectrometry (ICP-MS).

[0025] (3) Positive electrode active material layer forming paste preparation process In the preparation step of the paste for forming the positive electrode active material layer, the CNTs subjected to the magnetic separation step, the positive electrode active material, and the binder are mixed. The paste for forming the positive electrode active material layer may be prepared by further adding the positive electrode active material and the binder to the CNT paste subjected to the magnetic separation step and mixing them, or by recovering the CNTs selected in the magnetic separation step and mixing the CNTs, the positive electrode active material, and the binder with another appropriate solvent. In a preferred embodiment, the positive electrode active material and the binder are further added to the CNT paste subjected to the magnetic separation step and mixed. This allows the CNTs suitably dispersed in the CNT paste to be mixed with the positive electrode active material and the binder, and allows the secondary battery to have better output characteristics. At this time, the content of CNTs in the total solid content constituting the paste for forming the positive electrode active material layer is preferably 0.1% by mass or more and 3% by mass or less (preferably 0.35% by mass or more and 1.5% by mass or less, more preferably 0.35% by mass or more and 1% by mass or less).

[0026] The positive electrode active material can be one or more of the materials conventionally used in this type of secondary battery, without any particular limitation. For example, lithium transition metal oxides (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, etc.), lithium transition metal phosphate compounds (e.g., LiFePO4, etc.), etc. The properties of the positive electrode active material are not particularly limited, but are typically particulate. The average particle size of the particulate positive electrode active material is not particularly limited, and may be, for example, 25 μm or less (typically 1 μm or more and 25 μm or less, preferably 5 μm or more and 20 μm or less). The content of the positive electrode active material is preferably 50 mass% or more of the total solid content constituting the paste for forming the positive electrode active material layer, and may be, for example, 80 mass% or more and 99.5 mass% or less, or 85 mass% or more and 98.5 mass% or less. In this specification, the term "average particle size" refers to the particle size (D50, also called the median size) that corresponds to a cumulative frequency of 50 volume percent from the fine particle side with a small particle size in a volume-based particle size distribution based on a general laser diffraction / light scattering method.

[0027] The binder can be any material that has been conventionally used as a binder in this type of secondary battery without any particular limitation. For example, fluorine-based binders such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene (PTFE) and rubber-based binders such as styrene butadiene rubber (SBR) can be suitably used as the binder. The content of the binder is preferably 0.1% by mass or more and 3% by mass or less, and may be 0.2% by mass or more and 1.5% by mass or less, or may be 0.5% by mass or more and 1% by mass or less, based on the total solid content constituting the paste for forming the positive electrode active material layer.

[0028] The paste for forming the positive electrode active material layer may contain, as a solid content, substances other than the above-mentioned positive electrode active material and binder, to the extent that the technology disclosed herein is not significantly impaired. Examples of such substances include conductive materials other than CNTs and various additives. Examples of conductive materials other than CNTs include carbon black (e.g., acetylene black, furnace black, ketjen black, etc.), coke, etc.

[0029] (4) Positive electrode active material layer formation process In the positive electrode active material layer forming step, the positive electrode active material layer forming paste prepared above is applied to a positive electrode current collector to form a positive electrode active material layer on the positive electrode current collector. As the positive electrode current collector, metals and alloys thereof having good electrical conductivity, similar to current collectors used in the positive electrodes of conventional secondary batteries, can be used. As the positive electrode current collector, for example, an aluminum foil having a thickness of about 10 μm to 30 μm can be suitably used. The dimensions of the positive electrode current collector are not particularly limited and may be appropriately determined according to the battery design.

[0030] The application of the paste for forming the positive electrode active material layer can be carried out according to a conventional method. For example, the paste for forming the positive electrode active material layer can be applied to the surface of the positive electrode current collector using a device such as a slit coater, a die coater, a comma coater, a gravure coater, or a dip coater. The paste for forming the positive electrode active material layer can be applied to one side or both sides of the positive electrode current collector. The amount of the paste for forming the positive electrode active material layer applied is not particularly limited, and can be arbitrarily set according to the desired battery characteristics. For example, the amount of the paste for forming the positive electrode active material layer applied is 10 mg / cm2 on both sides. 2 ~50mg / cm 2 and preferably 11 mg / cm 2 ~44mg / cm 2 It is more preferable that:

[0031] After the above coating process, a drying process is usually performed to dry the applied paste for forming a positive electrode active material layer. The drying method is not particularly limited, but for example, the solvent can be evaporated (volatilized) from the positive electrode current collector coated with the paste for forming a positive electrode active material layer using a drying device such as a drying oven. The drying temperature and drying time can be appropriately set according to the amount of the solvent contained in the paste for forming a positive electrode active material layer, and are not particularly limited. For example, the drying temperature is preferably about 70°C to 200°C (typically 100°C to 180°C). As a result, a positive electrode active material layer is formed on the positive electrode current collector.

[0032] After the drying process, a pressing process may be carried out as necessary. In the pressing process, a positive electrode active material layer having a desired thickness, density, and porosity can be obtained. For example, by appropriately controlling the conditions of the pressing process, the porosity of the formed positive electrode active material layer can be adjusted to a desired value within a range of about 20% to 50%. As the pressing method, for example, a compression (pressing) method such as a conventionally known roll pressing method or a flat plate pressing method can be adopted. This can suitably reduce the resistance of the secondary battery. The porosity of the formed positive electrode active material layer can be determined by mercury intrusion porosity. The porosity of the formed positive electrode active material layer can also be adjusted by changing the compounding ratio and solid content rate of the paste for forming the positive electrode active material layer.

[0033] In this manner, a positive electrode having a positive electrode active material layer formed on a positive electrode current collector can be manufactured. The positive electrode obtained by the manufacturing method disclosed herein has the advantage of improving the output characteristics of a secondary battery. Hereinafter, one embodiment of a secondary battery (specifically, a lithium ion secondary battery) using a positive electrode obtained by the manufacturing method disclosed herein will be described with reference to the drawings.

[0034] 2. Manufacturing method of secondary batteries FIG. 2 is a vertical cross-sectional view of a lithium ion secondary battery according to an embodiment, and FIG. 3 is a diagram showing a schematic internal structure of the lithium ion secondary battery. The lithium ion secondary battery 100 shown in FIG. 2 is a sealed battery constructed by housing an electrode body 20 and a non-aqueous electrolyte (not shown) in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with a liquid injection hole (not shown) for injecting the non-aqueous electrolyte. The positive terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum.

[0035] 3, the electrode body 20 has a long sheet-like positive electrode 50 (hereinafter also referred to as "positive electrode sheet 50"), a long sheet-like negative electrode 60 (hereinafter also referred to as "negative electrode sheet 60"), and a long sheet-like separator 70 (hereinafter also referred to as "separator sheet 70"). The electrode body 20 may be, for example, a wound electrode body in which the positive electrode sheet 50 and the negative electrode sheet 60 are overlapped with two separator sheets 70 interposed therebetween and wound in the longitudinal direction. The electrode assembly 20 is not limited to a wound electrode assembly, and may be, for example, a laminated electrode assembly in which a predetermined number of positive electrode sheets and negative electrode sheets are alternately laminated with separator sheets interposed therebetween.

[0036] The positive electrode sheet 50 uses a positive electrode (positive electrode sheet) obtained by the above-mentioned manufacturing method. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides in this case) of a long positive electrode collector 52. The positive electrode active material layer non-forming portion 52a (i.e., a portion where the positive electrode collector 52 is exposed without the positive electrode active material layer 54 formed) is formed so as to protrude outward from both ends in the winding axis direction of the electrode body 20 (i.e., the sheet width direction perpendicular to the longitudinal direction). The positive electrode collector plate 42a is joined to the positive electrode active material layer non-forming portion 52a.

[0037] As shown in FIG. 3, the negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed on one or both sides (both sides in this case) of a long negative electrode collector 62 along the longitudinal direction. As the material of the negative electrode collector 62, a metal with good conductivity (e.g., copper, nickel, titanium, stainless steel, etc.) can be used as in the case of conventional secondary batteries. As the negative electrode collector 62, a copper foil of, for example, about 5 μm to 35 μm is preferable. The dimensions of the negative electrode collector 62 are not particularly limited and may be appropriately determined according to the battery design. The negative electrode active material layer non-forming portion 62a (i.e., a portion where the negative electrode collector 62 is exposed without the negative electrode active material layer 64) is formed so as to protrude outward from both ends in the winding axis direction of the electrode body 20 (i.e., the sheet width direction perpendicular to the longitudinal direction). The negative electrode collector plate 44a is joined to the negative electrode active material layer non-forming portion 62a.

[0038] The negative electrode active material layer 64 contains at least a negative electrode active material capable of inserting / extracting lithium ions, which are charge carriers. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon can be used. The negative electrode active material layer 64 can contain components other than the active material, for example, a binder or a thickener. As the binder, for example, styrene butadiene rubber (SBR) can be used. As the thickener, for example, carboxymethyl cellulose (CMC) can be used.

[0039] Although not particularly limited, when the entire solid content of the negative electrode active material layer 64 is taken as 100 mass%, the content of the negative electrode active material is preferably 60 mass% or more, for example, preferably 90 mass% or more to 99 mass%, and more preferably 92 mass% to 98 mass%. When a binder is used, the content of the binder in the negative electrode active material layer 64 is, for example, preferably 1 mass% to 10 mass%, and more preferably 1 mass% to 5 mass%. When a thickener is used, the content of the thickener in the negative electrode active material layer 64 is, for example, preferably 1 mass% to 10 mass%, and more preferably 1 mass% to 5 mass%.

[0040] The negative electrode active material layer 64 can be produced, for example, by applying a paste for forming a negative electrode active material layer, which is typically prepared by mixing the above-mentioned negative electrode active material, binder, and thickener with an appropriate solvent (e.g., ion-exchanged water), to the negative electrode current collector 62 and drying it. In addition, the thickness, density, and the like of the negative electrode active material layer 64 can be adjusted by carrying out a pressing process as necessary.

[0041] The separator sheet 70 is disposed between the positive electrode active material layer 54 of the positive electrode sheet 50 and the negative electrode active material layer 64 of the negative electrode sheet 60, and insulates the positive electrode active material layer 54 from the negative electrode active material layer 64. The separator sheet 70 is made of a porous resin base material. Examples of the resin base material include sheets (films) made of resins such as polyolefins such as polyethylene (PE) and polypropylene (PP), polyesters, polyamides, and cellulose. The separator sheet 70 may have a single-layer structure, or may have a structure in which two or more types of porous resin sheets having different properties and characteristics (thickness, porosity, etc.) are laminated (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator sheet 70 may also have a heat-resistant layer (Heat Resistant Layer: HRL layer) made of ceramic particles or the like on its surface. The HRL may be the same as a heat-resistant layer provided in a separator of a known non-aqueous electrolyte secondary battery, For example, it includes ceramic particles such as alumina, silica, boehmite, magnesia, and titania, and binders such as PVdF.

[0042] As shown in FIG. 3, one end of the positive electrode sheet 50 along the longitudinal direction is provided with a portion where the positive electrode active material layer 54 is not formed (a positive electrode active material layer non-forming portion 52a). Also, one end of the negative electrode sheet 60 along the longitudinal direction is provided with a portion where the negative electrode active material layer 64 is not formed (a negative electrode active material layer non-forming portion 62a). The electrode body 20 can be produced, for example, according to a known method. Specifically, for example, the positive electrode sheet 50 and the negative electrode sheet 60 are stacked with two separators 70 interposed therebetween to produce a laminate, which is then wound in the longitudinal direction. At this time, the positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are wound so as to protrude outward from both ends of the electrode body 20 in the winding axis direction. In this manner, the electrode body 20 can be produced. In order to obtain a flat wound electrode body as shown in FIG. 3, the laminate may be wound into a flat shape, or a cylindrical wound body of the laminate may be first produced and then pressed from the side to be flattened.

[0043] Next, the obtained electrode body 20 is electrically connected to a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, respectively. Then, the electrode body 20 to which the positive electrode terminal 42 and the negative electrode terminal 44 are connected is housed in a battery case 30, and an appropriate non-aqueous electrolyte is injected and the battery case 30 is sealed. In this manner, the lithium ion secondary battery 100 according to this embodiment can be constructed. The non-aqueous electrolyte may be the same as that of the conventional one, and is not particularly limited. The non-aqueous electrolyte is, for example, a non-aqueous electrolyte solution containing a non-aqueous solvent and a supporting salt. The non-aqueous solvent contains, for example, carbonates such as ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. The supporting salt is, for example, a fluorine-containing lithium salt such as LiPF6. In addition, the non-aqueous electrolyte may contain components other than the above-mentioned components, for example, film-forming agents such as lithium bis(oxalato)borate (LiBOB) and vinylene carbonate (VC), and gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB), as long as the effects of the present invention are not significantly impaired.

[0044] The lithium ion secondary battery 100 obtained in the above manner has the advantage of improved output characteristics. Such lithium ion secondary battery 100 can be used for various purposes. Suitable applications include a driving power source mounted on vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and battery electric vehicles (BEVs). The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of batteries are connected in series and / or parallel.

[0045] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0046] <Test Example> 1. First test (1) Example 1 First, CNTs and a copolymer containing a pyrene aromatic unit as a dispersant were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a CNT paste. The CNTs were multi-walled carbon nanotubes manufactured by chemical vapor deposition using Co as a catalytic metal, and had an average diameter of 10 nm to 20 nm and an average length of 0.5 μm to 5 μm. Next, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 and polyvinylidene fluoride (PVdF) as a binder were prepared. The positive electrode active material, CNT, and PVdF were mixed in the CNT paste so that the mass ratio of the positive electrode active material:CNT:PVdF was 99.15:0.35:0.50, to prepare a paste for forming a positive electrode active material layer. The paste for forming a positive electrode active material layer was applied to both sides of an aluminum foil, dried, and pressed to obtain a positive electrode in which a positive electrode active material layer was formed on a positive electrode current collector. The weight of both sides of the formed positive electrode was 44 mg / cm. 2 The porosity measured by mercury intrusion porosimetry was 20%.

[0047] A paste for forming a negative electrode active material layer was prepared by mixing graphite (C) as a negative electrode active material, CMC as a thickener, and SBR as a binder with ion-exchanged water in a mass ratio of C:CMC:SBR=98:1:1. The paste for forming a negative electrode active material layer was applied to both sides of a copper foil, dried, and pressed to obtain a negative electrode in which a negative electrode active material layer was formed on a negative electrode current collector. As the separator, a polypropylene sheet having a single layer structure was used. The positive and negative electrodes thus produced were stacked with the separator thus prepared therebetween to produce a stacked electrode body.

[0048] The positive and negative electrode terminals were connected to the laminated electrode body prepared above, and the laminated electrode body was housed in a square battery case having an electrolyte injection hole. Then, a non-aqueous electrolyte was injected through the injection hole of the battery case, and the injection hole was sealed airtight. The non-aqueous electrolyte was prepared by adding 1 mass % of vinylene carbonate (VC) to a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of EC:DMC:EMC=3:4:3, and dissolving LiPF6 as a supporting salt at a concentration of 1.15 mol / L. Then, an activation process was performed to obtain a secondary battery for evaluation of Example 1.

[0049] (2) Example 2 The same CNTs as in Example 1 and a copolymer containing a pyrene aromatic unit as a dispersant were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a CNT paste. Next, a magnetic separation process was carried out so that the metal content in the selected CNTs was 2 mass% when the total of CNTs and metals was 100 mass%. Specifically, the CNT paste was passed once through a magnetic separator using a neodymium magnet (permanent magnet) with a magnetic flux density of 400 millitesla (mT). For the above CNT paste, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and polyvinylidene fluoride (PVdF) as a binder were mixed in a mass ratio of positive electrode active material:CNT:PVdF=99.15:0.35:0.50 to prepare a paste for forming a positive electrode active material layer. The paste for forming a positive electrode active material layer was applied to both sides of an aluminum foil, dried and pressed to obtain a positive electrode in which a positive electrode active material layer was formed on a positive electrode current collector. The weight of both sides of the formed positive electrode was 44 mg / cm. 2 The porosity measured by mercury intrusion porosimetry was 20%. A secondary battery for evaluation of Example 2 was produced in the same manner as in Example 1, except for the above positive electrode.

[0050] (3) Examples 3 to 5 The number of times the CNTs were passed through the magnetic separator was changed so that the metal content (mass%) in the CNTs separated in the magnetic separation step, when the total of the CNTs and metals was taken as 100 mass%, would be the value shown in Table 1. Except for this, the evaluation secondary batteries of Examples 3 to 5 were produced in the same manner as in Example 2.

[0051] (4) Example 6 The same CNTs as in Example 1 were passed in a powder state four times through a magnetic separator using a neodymium magnet (permanent magnet) with a magnetic flux density of 400 millitesla (mT). A secondary battery for evaluation in Example 6 was produced in the same manner as in Example 1, except for this.

[0052] (5) Example 7 The same CNTs as in Example 1 were treated with nitric acid, filtered, and used as the conductive material. A secondary battery for evaluation in Example 7 was produced in the same manner as in Example 1 except for this.

[0053] (6) Output resistance evaluation Each evaluation secondary battery was adjusted to a SOC (State of charge) of 50% by constant current constant voltage (CC-CV) charging, and then placed in an environment of 25°C. Discharge was performed for 10 seconds at a current value of 5C, and the voltage drop ΔV at this time was obtained. The output resistance value of each evaluation secondary battery was calculated using this voltage drop ΔV and the current value. The results are shown in Table 1.

[0054] [Table 1]

[0055] As shown in Table 1, by preparing the CNT paste and performing the magnetic separation process, the output resistance value is lowered compared to Example 1, in which the magnetic separation process was not performed, and Example 6, in which the magnetic separation process was performed in the powder state. This is presumed to be because the dispersant contained in the CNT paste makes the metal present in the CNTs slippery by performing the magnetic separation process in the CNT paste state, facilitating the removal of the metal. In addition, as shown in Example 7, by removing the metal by washing with nitric acid, the metal content in the CNT after the nitric acid washing is 0 mass%, but the output resistance value is higher than that of Example 3, in which the metal content is 1.6 mass%. In other words, it is presumed that when the metal is removed by washing with nitric acid, the CNTs are damaged, thereby reducing the conductivity of the CNTs. Therefore, by preparing a CNT paste containing at least CNTs and a dispersant, applying a magnetic force to the CNT paste to adsorb the metal present inside the CNTs, and performing a magnetic separation process to separate the CNTs from the metal, and then manufacturing a positive electrode using the CNTs that have undergone the magnetic separation process as a conductive material, it is possible to manufacture a positive electrode that imparts excellent output characteristics to a secondary battery.

[0056] It can also be seen that the output resistance value is smaller in Examples 3 to 5, in which the magnetic separation step was performed so that the metal content in the CNTs after the magnetic separation step was 1.6 mass% or less. This is presumably because when the metal content in the sorted CNTs is 1.6 mass% or less, the metal present inside the CNTs is also suitably removed. This makes it easier for the nonaqueous electrolyte to penetrate into the CNTs, and also facilitates the movement of Li ions, which is presumably why the output resistance value is lowered.

[0057] 2. Second test In the second test, the output resistance of the secondary battery was evaluated when the composition ratio of the positive electrode, the area coverage on both sides, and the porosity were changed from those in the first test.

[0058] (1) Example 11 First, CNTs and a copolymer containing a pyrene aromatic unit as a dispersant were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a CNT paste. The CNTs were multi-walled carbon nanotubes manufactured by chemical vapor deposition using Co as a catalytic metal, and had an average diameter of 10 nm to 20 nm and an average length of 0.5 μm to 5 μm. Next, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and polyvinylidene fluoride (PVdF) as a binder were prepared. The positive electrode active material:CNT:PVdF were mixed in the above CNT paste so as to have a mass ratio of 98.3:1.0:0.7, to prepare a paste for forming a positive electrode active material layer. The paste for forming a positive electrode active material layer was applied to both sides of an aluminum foil, dried, and pressed to obtain a positive electrode in which a positive electrode active material layer was formed on a positive electrode current collector. The weight of both sides of the formed positive electrode was 11 mg / cm. 2 The porosity measured by mercury intrusion porosimetry was 50%.

[0059] A paste for forming a negative electrode active material layer was prepared by mixing graphite (C) as a negative electrode active material, CMC as a thickener, and SBR as a binder with ion-exchanged water in a mass ratio of C:CMC:SBR=98:1:1. The paste for forming a negative electrode active material layer was applied to both sides of a copper foil, dried, and pressed to prepare a negative electrode. As the separator, a polypropylene sheet having a single layer structure was used. The positive and negative electrodes thus produced were stacked with the separator thus prepared therebetween to produce a stacked electrode body.

[0060] The positive and negative electrode terminals were connected to the laminated electrode body prepared above, and the laminated electrode body was housed in a square battery case having an electrolyte injection hole. Then, a non-aqueous electrolyte was injected through the injection hole of the battery case, and the injection hole was sealed airtight. The non-aqueous electrolyte was prepared by adding 1 mass % of vinylene carbonate (VC) to a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of EC:DMC:EMC=3:4:3, and dissolving LiPF6 as a supporting salt at a concentration of 1.15 mol / L. Then, an activation treatment was performed to obtain a secondary battery for evaluation of Example 11.

[0061] (2) Example 12 The same CNT as in Example 11 and a copolymer containing a pyrene aromatic unit as a dispersant were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a CNT paste. Next, a magnetic separation process was carried out so that the metal content in the selected CNT was 2 mass% when the total of the CNT and the metal was taken as 100 mass%. Specifically, the CNT paste was passed once through a magnetic separator using a neodymium magnet (permanent magnet) with a magnetic flux density of 400 millitesla (mT). For the above CNT paste, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 and polyvinylidene fluoride (PVdF) as a binder were mixed in a CNT paste so that the mass ratio of the positive electrode active material:CNT:PVdF was 98.3:1.0:0.7, to prepare a paste for forming a positive electrode active material layer. The paste for forming a positive electrode active material layer was applied to both sides of an aluminum foil, dried, and pressed to obtain a positive electrode in which a positive electrode active material layer was formed on a positive electrode current collector. The weight of both sides of the formed positive electrode was 11 mg / cm. 2 The porosity measured by mercury intrusion porosimetry was 50%. A secondary battery for evaluation of Example 12 was produced in the same manner as in Example 11 except for the above positive electrode.

[0062] (3) Examples 13 to 15 The number of times the CNTs were passed through the magnetic separator was changed so that the metal content (mass%) in the CNTs separated in the magnetic separation step, when the total of the CNTs and metals was taken as 100 mass%, would be the value shown in Table 2. Except for this, the evaluation secondary batteries of Examples 13 to 15 were produced in the same manner as in Example 12.

[0063] (4) Example 16 The same CNTs as in Example 11 were passed in a powder state four times through a magnetic separator using a neodymium magnet (permanent magnet) with a magnetic flux density of 400 millitesla (mT). A secondary battery for evaluation in Example 16 was produced in the same manner as in Example 11 except for this.

[0064] (5) Example 17 The same CNTs as in Example 11 were treated with nitric acid, filtered, and used as the conductive material. A secondary battery for evaluation in Example 17 was produced in the same manner as in Example 11 except for this.

[0065] (6) Output resistance evaluation Each evaluation secondary battery was adjusted to a SOC (State of charge) of 50% by constant current constant voltage (CC-CV) charging, and then placed in an environment of 25°C. Discharge was performed for 10 seconds at a current value of 5C, and the voltage drop ΔV at this time was obtained. The output resistance value of each evaluation secondary battery was calculated using this voltage drop ΔV and the current value. The results are shown in Table 2.

[0066] [Table 2]

[0067] As shown in Table 2, even when the composition ratio, basis weight, and porosity of the positive electrode active material layer are changed, the output characteristics of the secondary battery are improved by preparing a CNT paste, performing magnetic separation on the CNT paste, and separating the CNTs from the metal.

[0068] Although specific examples of the technology disclosed herein have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]

[0069] 20 Electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 100 Lithium-ion secondary battery

Claims

1. A method for producing a positive electrode of a secondary battery, comprising the steps of: A CNT paste preparation step of preparing a CNT paste containing at least carbon nanotubes (CNTs) and a dispersant; a magnetic separation step of applying a magnetic force to the CNT paste to adsorb metal present inside the CNT and separate the CNT from the metal; a positive electrode active material layer forming paste preparation step of mixing the CNTs subjected to the magnetic separation step, a positive electrode active material, and a binder to prepare a positive electrode active material layer forming paste; a positive electrode active material layer forming step of applying the prepared positive electrode active material layer forming paste to a positive electrode current collector to form a positive electrode active material layer on the positive electrode current collector; Inclusive of The metal includes at least one of chromium (Cr), nickel (Ni) and cobalt (Co); The magnetic separation step is carried out so that the content of the metal in the sorted CNT is 1.6% by mass or less when the total of the CNT and the metal is 100% by mass. A method for manufacturing a positive electrode.

2. The CNTs before the magnetic separation step have a metal content of 4.0 mass% or more. The method of claim 1 .

3. A secondary battery is constructed using the positive electrode produced by the production method according to claim 1 or 2. A method for manufacturing a secondary battery.